Gallery Walk and Think-Pair-Share Techniques for Teaching Writing Descriptive Text to Students with High and Low Motivation - Dewi Kilas Sinar Nurani, Arsianti; Rukmini, Dwi (English Education Journal, 2017)
This study investigates the effectiveness of gallery walk and think-pair-share techniques to teach writing descriptive text to students with high and low motivation. A quantitative approach is used in this study by applying 2x2 factorial design in the form of pre-test and post-test. 72 students from the tenth grade of State Senior High School 1 Simo Boyolali who take English subject in the academic year of 2016/2017 are participated in this study. The motivational questionnaire and writing test are used as the instruments of the study. This study reveals several findings: gallery walk technique is effective to teach writing descriptive text to students with high and low motivation, think-pair-share technique is effective to teach writing descriptive text to students with high and low motivation, there is no significant difference on the effect of gallery walk technique and think par-share technique towards writing descriptive text achievement of students with high and low motivation, gallery walk technique is more effective to be used to teach writing descriptive text to students with high and low motivation compared to think-pair-share technique,  the ANOVA test reveals that there is no effective interaction among studentsâ motivation, teaching technique, and studentsâ writing achievement. To conclude, gallery walk technique is more effective compared to think-pair-share technique for teaching writing descriptive text to students with high and low motivation, and there is no effective interaction among studentsâ motivation, teaching technique and studentsâ writing achievement. In sum, it can be said that studentsâ writing achievement is not influenced by motivation; it is influenced by the implementation of teaching techniques.